Fed cattle market is guardedly optimistic, says K-State's Sands - M. Sands (Kansas Agricultural Experiment Station Research Reports, 1982)
Returns to cattle feeders should move back into the profit column during most of 1982. but feeding margins will remain narrow, says Mike Sands, extension economist specializing in livestock marketing at K-State. "Most of the improvement in profitability compared with last year will result from lower feed and feeder prices, rather than a dramatic rise in fed cattle prices." he points out. With Choice steer prices expected to average in the $64-66 cwt. range during January-June. feeding returns should average on the positive side, in sharp contrast to the average $95-per-head losses suffered during the first half of 1981. Sands believes. Total commercial cattle slaughter reached 34.9 million head in 1981. about 3% larger than a year earlier. Although fed cattle marketings dropped about 1% from 1980 levels, the decline was more than offset by a 14% rise in nonfed steer and heifer and cow slaughter. "Certainly, the lack of growth in consumers' inflation-adjusted incomes during the past year has contributed to the dismal economic performance of the cattle industry," Sands comments. "But, perhaps more importantly, total red meat and poultry supplies climbed to a record 53.1 billion lbs. in 1981. about 1.5% more than the year-earlier record.
Keywords: Cattlemen' s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Market; Cattle inventory; Feeder cattle